2019
DOI: 10.18203/2349-3291.ijcp20194738
|View full text |Cite
|
Sign up to set email alerts
|

A study on screen time use in children between 24 to 60 months of age in Tamilnadu, India

Abstract: Background: This study was done with the objective of finding the average daily duration and pattern of screen time use in children in the age group of 24 to 60 months in the state of Tamilnadu, India and to find the correlation between screen time and demographic parameters.Methods: This cross-sectional observational study was conducted at the state of Tamilnadu, India from June 2019 to August 2019 among 148 children in play school and kindergarten classes in the age group of 24 to 60 months fulfilling the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
3
1
0
Order By: Relevance
“…Our study demonstrated similarly, with an average screen use of 2.1 h per day and 89.9% exceeding the AAP recommendations. Similar to most published literature, we found that the commonest screen used was TV (76.7%), and the type of content most watched were cartoons (82.5%) [12,21]. We found children who used devices other than a computer were 6.5 times more likely to have excess screen time.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our study demonstrated similarly, with an average screen use of 2.1 h per day and 89.9% exceeding the AAP recommendations. Similar to most published literature, we found that the commonest screen used was TV (76.7%), and the type of content most watched were cartoons (82.5%) [12,21]. We found children who used devices other than a computer were 6.5 times more likely to have excess screen time.…”
Section: Discussionsupporting
confidence: 86%
“…According to 2 other studies from India, less than 20% of preschool children use a screen for less than 1 h a day [12,13]. Our study demonstrated similarly, with an average screen use of 2.1 h per day and 89.9% exceeding the AAP recommendations.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We found that children who used screen for more than 1 hour a day interacted more with their playmates and older family members as compared to children with lesser screen use, however, this was not signi cant. Compliance with the AAP recommendations for screen-time is poor as per two other studies from the Indian subcontinent, who demonstrated less than 20% of the preschool population limiting screen use to less than 1 hour a day [11,12]. Our study demonstrated similar data, with an average screen use of 2.14 hours per day and only 11% complying with the AAP recommendations.…”
Section: Resultssupporting
confidence: 68%
“…In our study, age, gender, residence and socioeconomic status had no influence on screen time. This is similar to studies by Shirley SA, et al19 and Varadarajan S, et al1 .Parental knowledge and perceptions on the effect of screen time highly influences screen time behaviour in children. In a study by Shirley SA, et al19 on the attitude and awareness among parents, majority of parents seemed to be concerned about screen time of children23 .…”
supporting
confidence: 90%